Gestão de políticas públicas relacionadas à infraestrutura regional logística de transporte : uma análise do município de Barra do Garças-MT - Noleto, Rogério Marcondes (2022)
This study discusses the development of public policies related to logistics and regional infrastructure of road transport in the State of Mato Grosso, more specifically, in the Immediate Region of Barra do Garças-MT. The transport structure is of paramount importance for the economic and social development of cities, being responsible for planning how to meet the needs related to the movement of people and the transport of goods. In view of this, means of transport are indispensable and fundamental for the economic development of any region, but, for this, it is important to develop public policies and investments aimed at improving transport infrastructure with a view to integration between regions, enabling the improving the transit conditions for products and people, in addition to promoting the expansion of local commerce and socio-economic development. Our research was carried out in the municipality of Barra do Garças-MT, where we analyzed the conditions of the transport infrastructure. The general objective of this work was to analyze the situation of the road transport infrastructure in the municipality of Barra do Garças-MT in order to understand how the management of public policies, responsible for this issue, has been leading this aspect to respond to the necessary transport demands to its growth. The specific ones were: 1) To analyze the public policies currently applied in the transport infrastructure of the municipality of Barra do Garças-MT; 2) Understand the logistical pattern of transport and the ways in which the products transit in the municipality of Barra do Garças-MT; 3) Discuss what should be implemented for the economic improvement of transport costs for the municipality. For this, the methodology used was qualitative and exploratory, while the methodological procedures were based on the reading of authors who deal with the topic, in interviews and also on the google forms application platform for the collection and analysis of data collected from the research participants.